GAMBARAN PERENCANAAN DAN PENGANGGARAN PROGRAM KESEHATAN IBU DAN ANAK DI DINAS KESEHATAN PROVINSI JAWA TIMUR TAHUN 2022 - Pratiwi, Ika Ajeng; Sinthya Ulandari, Luh Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 3 (2022): Desember 2022DO - 10.24843/ACH.2022.v09.i03.p11, 2022)
ABSTRACT MCH in East Java Province has not run optimally. Planning and budgeting have a very important role in the success of a program, especially for the MCH program which has the potential to reduce MMR and IMR. The purpose of this study was to describe the planning and budgeting of maternal and child health programs at the East Java Provincial Health Office in 2022. This research is a qualitative research through descriptive case studies, using qualitative data. The data analysis technique in this study used thematic analysis. There were four informants in this study, including the Head of the PPA Subdivision, the Head of the Public Health Service, the Head of the KGM Section, and the KGM Staff. The results showed that the situation analysis of all informants stated that they were influenced by health problems, program performance, environmental behavior factors. Determination of goals adjusts to the objectives of the President, Governor, and the Health Service. The identification of activities is divided into four activities such as the P2KT module version 3. Budget calculations are linked to targets and MSS. Budget adequacy is not directly proportional to the achievement of program targets because there are other factors that influence it. Keywords : Maternal and Child Health, MCH, Planning and Budgeting